1996
DOI: 10.1111/j.1651-2227.1996.tb14289.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment of short children born small for gestational age: metanalysis of four independent, randomized, controlled, multicentre studies

Abstract: A minority of children born small for gestational age (SGA) fail to achieve sufficient catch-up growth during infancy and remain short throughout childhood. apparently without being growth hormone (GH) deficient. The effect of GH administration was evaluated over 2 years in short prepubertal children born SGA. The children (n = 244). who were taking part in four independent multicentre studies, had been randomly allocated to groups receiving either no treatment or GH treatment at a daily dose of 0.1.0.2 or 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
4
6

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 19 publications
(4 reference statements)
7
47
4
6
Order By: Relevance
“…Moreover, we found that age at start and the duration of GH treatment were the strongest variables correlating with height gain. These results agree also with the study of Sas et al (13), as well as the results from meta-analysis of four European trials (15), although neither is yet to adult height.…”
Section: Final Height In Short Sga On Ghsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, we found that age at start and the duration of GH treatment were the strongest variables correlating with height gain. These results agree also with the study of Sas et al (13), as well as the results from meta-analysis of four European trials (15), although neither is yet to adult height.…”
Section: Final Height In Short Sga On Ghsupporting
confidence: 82%
“…Most studies report correlations with age at start of GH treatment (13,16,30), one with height SDS at start (30) and others with the prepubertal GH dose (13,15,16,30). We observed no correlation between response to GH and pretreatment height velocity.…”
Section: Final Height In Short Sga On Ghcontrasting
confidence: 45%
See 1 more Smart Citation
“…Although highdose GH treatment may have induced some degree of insulin resistance, no significant alterations in fasting blood glucose or hemoglobin A1c were identified after 2 years (11).…”
Section: Study Design Materials and Methodsmentioning
confidence: 99%
“…We summarize recent growth data from four independent, randomized, controlled, multicenter studies exploring the effects of three doses of daily GH administration over two years in short children born small for gestational age (11).…”
Section: Introductionmentioning
confidence: 99%